IRELAND, Daryl R. John Song: Modern Chinese Christianity and the Making of a New Man. - Anderson, Allan Heaton (PentecoStudies, 2022)
IRELAND, Daryl R. John Song: Modern Chinese Christianity and the Making of a New Man. Waco, Texas: Baylor University Press, 2020. xix + 248 pp. Hbk. ISBN: 9781481312707. £36.